Lynch syndrome and cervical cancer. Issue 11 (14th July 2015) - Antill, Yoland C.; Dowty, James G.; Win, Aung Ko; Thompson, Tina; Walsh, Michael D.; Cummings, Margaret C.; Gallinger, Steven; Lindor, Noralane M.; Le Marchand, Loïc; Hopper, John L.; Newcomb, Polly A.; Haile, Robert W.; et al.
Abstract : Carriers of germline mutations in DNA mismatch repair (MMR) genes are at increased risk of several cancers including colorectal and gynecologic cancers (Lynch syndrome). There is no substantial evidence that these mutations are associated with an increased risk of cervical cancer. A total of 369 families with at least one carrier of a mutation in a MMR gene (133 MLH1, 174 MSH2, 35 MSH6 and 27 PMS2 ) were ascertained via population cancer registries or via family cancer clinics in Australia, New Zealand, Canada, and USA. Personal and family histories of cancer were obtained from participant interviews. Modified segregation analysis was used to estimate the hazard ratio (incidence rates for carriers relative to those for the general population), and age‐specific cumulative risks of cervical cancer for carriers. A total of 65 cases of cervical cancer were reported (including 10 verified by pathology reports). The estimated incidence was 5.6 fold (95% CI: 2.3–13.8; p  = 0.001) higher for carriers than for the general population with a corresponding cumulative risk to 80 years of 4.5% (95% CI: 1.9–10.7%) compared with 0.8% for the general population. The mean age at diagnosis was 43.1 years (95% CI: 40.0–46.2), 3.9 years younger than the reported USA population mean of 47.0 years ( p  = 0.02). Women with MMR gene mutations were found to have an increased risk of cervical cancer. Due to limited pathology verification we cannot be certain that a proportion of these cases were not lower uterine segment endometrial cancers involving the endocervix, a recognized cancer of Lynch syndrome. Abstract : What's new? Women with DNA mismatch repair gene mutations (Lynch syndrome) are at increased risk for several cancers but it is unclear whether cervical cancer is one of them. Using data from international cancer registries the authors show that women with Lynch syndrome have an increased risk of cervical cancer that is six times higher than the general population. Carriers of cervical cancers were diagnosed on average four years earlier than the general population, pointing to cervical cancers as part of Lynch syndrome spectrum cancers.